PENGARUH DIGITALISASI ARSIP DAN KOMPETENSI TENAGA ADMINISTRASI TERHADAP EFISIENSI ADMINISTRASI SEKOLAH - Aripurnomo Artiyanto; Shalahuddin, Shalahuddin (Nusantara Hasana Journal, 2026)
This research examines how the transition to digital archiving and the proficiency of administrative personnel impact operational effectiveness within educational settings. The study is driven by the increasing necessity for streamlined and productive administrative workflows in schools, emphasizing the vital synergy between technological tools and human capability. The primary objective is to determine the extent to which digital systems and staff expertise contribute to enhancing school management performance. Utilizing a quantitative methodology, data were gathered from a sample of 30 staff members, involving rigorous instrument validation and regression modeling to identify variable correlations. The findings reveal that archive digitalization and administrative competence exert a substantial positive influence on school efficiency, both independently and in combination. Statistically, the regression analysis confirms that these two factors account for 65.9% of the efficiency variance, while the remaining 34.1% is attributed to external variables not covered in this study.The findings highlight the importance of combining technological innovation with human resource development to achieve optimal efficiency in school administration. This study implies that schools should strengthen digital archiving systems while continuously enhancing staff competence to ensure sustainable improvements in administrative performance.